ByzRev 01.2019.009: Annemarie Luijendijk – William E. Klingshirn (eds.), My Lots are Thy Hands: Sortilege and its Practitioners in Late Antiquity - Filimon, Florin (The Byzantine Review, 2019)
Annemarie Luijendijk – William E. Klingshirn (eds.), My Lots are Thy Hands: Sortilege and its Practitioners in Late Antiquity (Religions in the Graeco-Roman World 188). Leiden – Boston: Brill 2018. xvii, 392 pp. – ISBN: 978-90-04-38410-1 (129 EURO).